Reflections on a study of Intercultural Education and Participation in Mapuche Communities in the IX Region of La Araucania, Chile - Williamson, Guillermo; Pastrana, Jill Pinkney; Gómez, Patricia (Education Policy Analysis Archives, 2005)
This analysis focuses on a specific dimension of the "indigenous question" in Chile: that of social participation in educational processes, specifically within the context of the current national education reform. Beginning with new understandings based on the work of the Proyecto de Investigación & Desarrollo, Gestión Participativa en Educación-Kelluwün, this paper analyzes the possibilities and limits of participation, considering the particular framework of institutional structures inherited from the Military Regime, characteristics of the education reform, and the context of current indigenous conflicts for territorial and political rights. The Proyecto Kelluwün, using methods of action research and based on the principles of Paulo Freire, developed diverse experiences oriented to the augmentation of action, dialogue, critical reflection and elevating the social power of the community as an actor able to confront the local government, the aim being the integration of Mapuche culture, language and cosmovision into the curriculum, pedagogy, organization and culture of local schools. Through the understandings generated in the process of engaged research, we interrogate the real possibilities of increasing effective participation in actual contexts–participation, social engagement aimed at attaining the objectives of the quality and equity sought by the current educational reform as well as the expansion of community rights sought by the Mapuche in Chile.